ANALISIS PENGARUH KOMPETENSI SUMBER DAYA MANUSIA, TRANSPARANSI DAN PEMANFAATAN TEKNOLOGI INFORMASI TERHADAP PENYUSUNAN ANGGARAN PENDAPATAN DAN BELANJA DAERAH DI KOTA MEDAN - IRNA TRIANNUR LUBIS; YUNI SHARA (JURNAL ILMIAH SIMANTEK, 2021)
This study aims to find out the factors that affect the constituents of APBD in the city of Medan. The data used is primarydata using questionnaires given to all accounting entities in the Medan City Government environment of 34 Regional DeviceOrganizations (OPD). The results of the analysis showed that the competence of human resources and the utilization ofinformation technology had a significant effect on the preparation of APBD, while transparency had no significant effect onthe preparation of APBD. The results of this study suggest that the Medan City Government pay attention to human resourcecompetence, transparency.